Linguistic Landscapes and Communication Strategies to Promote Cultural Heritage Tourism - Liya Umaroh; Mukaromah Mukaromah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The goal of this research is describing the relationship between language landscapes and communication strategies to promote cultural heritage tourism. To analyze the data a research method was selected using descriptive qualitative with collecting data through dept interview, observation, and photographing. Meanwhile Linguistic landscapes uses as the object of this research and the result shows that lingustic landscapes and communication strategies can be intertwined to promote cultural heritage tourism.